FUNDAMENTAL AND CLINICAL STUDIES OF 6059-S IN SURGICAL FIELD - TAKENAKA, NOBUO; TANAKA, TOYOHARU; ISHIDA, MOTOHIKO; KATOH, SHIGETSUGU (CHEMOTHERAPY, 1980)
Biliary concentrations of 6059-S after intravenous injection of 1 g were assayed in 3 cases, and high peak level of 139μg/ml in mean value was observed after 2 hours. 6059-S was administered to 12 cases of infection (11 cases of superficial soft tissue infection and one case of perforative peritonitis) and one case of prophylactic use for burn.The clinical response of the drug in 12 cases of infection was excellent in 6 cases, good in 3 cases and fair in 4 cases with 75.0% of efficacy, and the result of prophylactic use was effective. Bacteriologically, all causative organisms were eradicated in 4 cases of S.aureus, one case of S.epidermidis and one case of E.coli mixed with Bacteroides. No side effect nor adverse reaction on blood and blood chemistry was observed in these cases.